Utilization of Benefits of Developmental Programmes by Agricultural Labour Households in Karnataka-an Institutional Economic Analysis - Venu, B. N.; Umesh, K. B.; Olekar, Jagannath; Reddy, B. V. Chinnappa (International Journal of Bio-resource and Stress Management, 2017)
Good governance is crucial for inclusive growth. In this study access to benefits and spread of the benefits from various Government programmes is compared among migration and non-migration labours in irrigated and rainfed regions of Karnataka. Generally the developmental programs are more focused towards welfare of the intended labour households. All the labour households of irrigated situation were getting benefits under BPL card legally. In rainfed situation, on an average 95% of labour households benefited through BPL card. Due to low or no participation in Co-operatives by rainfed labour households the Yashasvini card benefit was less compare to irrigated situation. Due to lower level of income and illiteracy of the labour households, they were not able to send their children to study in private schools. Therefore most of the labour households availed benefit under programmes like Mid-Day Meal Scheme and Kaliyuva Makkalige Bicycle schemes. Average annual benefit received by the agricultural labour households through various programmes was high in irrigated (Rs. 19,550) compared to rainfed situation (Rs. 19,391). All the labour households in both the situations incurred highest transaction cost while getting benefit from the rural housing schemes. The transaction cost for getting benefit was zero for the programmes like Mid-Day Meal and Kaliyuva Makkalige Bicycle which was free of any rent.